Retrofitting of Box Section Concrete Beams to Resist Shear and Torsion Using Near-Surface-Mount (NSM) GFRP Stirrups (Fracture and Structural Integrity, 2023)
There are a few kinds of research about box section Reinforced Concrete (RC) beams under the effect of combined shear and torsional stresses. In the present research, the concept of adding external strengthening, in the transverse direction, is adopted. The paper focuses on using Glass Fiber Reinforced Polymer GFRP ropes as near-surface mount stirrups. Nine box-section concrete specimens were decanted and tested. Three variables are adopted, (1) GFRP stirrups diameter, (2) GFRP stirrups inclination, and (3) GFRP stirrups spacing. The experimental results showed considerable enhancement in the shear capacity of the strengthened beams by 8 to 56% depending on the effectiveness of the studied parameters. Ductility and toughness were improved when more intensive strengthening schemes were adopted. The shear capacity of all tested beams based on Egyptian code ECP 208–2019 is calculated and compared with that from American code ACI 440–2019 and Canadian code CSA-A23.3-04. The shear capacity from both Egyptian and American codes compared with experimental loads. The analytical results are conservative in some cases and unconservative in others while the analytical results in general are conservative. The Canadian code CSA-A23.3-04 is unconservative compared to the experimental results for the range of the studied parameters and specimens.
Keywords: Experimental; Analytical; Reinforced concrete box section beams; Near-surface mount (NSM); Retrofitting; Shear and torsion; glass- fiber-reinforced polymer (GFRP)